Factors influencing attributions to prejudice: harm, intent, and individual differences in the propensity to make attributions to prejudice - Miller, Stuart S. (Kansas State University, 2014)
In recent American culture, expressions of racial prejudice have become increasingly subtle and ambiguous. Given such ambiguity, whether or not prejudice is perceived by observers may be related to individual differences in the tendency to make attributions to prejudice. The present set of studies test the hypothesis that the beliefs and expectations related to a propensity to make attributions to prejudice are moderated by different information about harm and intent that have been shown in previous research to influence observers’ attributions of prejudice. Study 1 manipulated information about the harm caused by a White actor to a Black target (no harm, ambiguous harm, clear harm). Study 2 manipulated information about a White actor’s intent to racially discriminate against a Black target (no intent, ambiguous intent, clear intent). Across both studies, evidence supported the conclusion that attributions of prejudice are related to observers’ beliefs and expectations about racial prejudice when they are given ambiguous information about harm and intent. Understanding when differences in observers’ propensity to make attributions to prejudice might influence their attributions will contribute to our understanding of when expressions of prejudice are perceived, and more generally about how and when beliefs influence how individuals interpret their social world.
Keywords: Attribution; Prejudice; Individual; Differences; Psychology (0621)